Optical determinations of photophysiology along an ecological gradient in the North Pacific Ocean - James G. Allen; Mathilde Dugenne; Ricardo M. Letelier; Angelicque E. White (Limnology and Oceanography, 2022)
Photosynthesis acts as a fundamental control in the cycling of biologically reactive elements in the ocean. Modeling photosynthesis requires an understanding of its response to light, specifically the maximum rate of photosynthesis per photon absorbed and the irradiance level at which it becomes light‐saturated ( E k ), though field measurements of these parameters are both time and labor intensive. As absorbed light either drives photosynthesis, is re‐emitted as fluorescence, or is converted to heat, fluorescence can be related to the photosynthetic response to light in that, as light increases, there exists an inflection point where the probability that excess absorbed energy is dissipated as heat increases and fluorescence yield is decreased. Accordingly, we use a combination of in vivo chlorophyll fluorescence, particulate matter absorption spectra, and photosynthetically active radiation measurements to approximate this inflection irradiance (termed E FT ) and relate it to modeled E k along a transect from the oligotrophic North Pacific Subtropical Gyre to the edge of the more eutrophic subpolar gyre (~ 45°N). We find that E FT declines by a factor of 4× from values of 200–300 μ mol photons m −2 s −1 in the oligotrophic gyre to 50–100 μ mol photons m −2 s −1 north of the transition zone and correlates well with E k from traditional data and models. This latitudinal pattern is associated with changes in biomass concentrations and the phytoplankton carbon to chlorophyll ratio, as well as with changes in particulate carbon to nitrogen ratios. Collectively, these results demonstrate a promising framework to capture high‐resolution variability in a key photosynthetic parameter.